2021
DOI: 10.1155/2021/8774010
|View full text |Cite
|
Sign up to set email alerts
|

Life-Threatening Retroperitoneal Hematoma in a Patient with COVID-19

Abstract: COVID-19 is a respiratory illness that affects the human body in many different ways. The disease carries both thrombotic and hemorrhagic complications, especially in those patients who are anticoagulated to prevent the thromboembolic manifestations. In this report, we discuss a case of retroperitoneal hemorrhage in a patient treated with therapeutic anticoagulation which ultimately led to the patient’s death. The literature highlights the importance of anticoagulation because it reduces mortality in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Recently, RPHs have been reported in patients with COVID-19 where an anticoagulant has been used. Most patients were treated using embolization where there was a clear bleeding focus [6][7][8][14][15][16]. In this study, no obvious bleeding focus was observed on the CT scan, and the ECMO flow was not properly maintained due to external compression by a huge RPH.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Recently, RPHs have been reported in patients with COVID-19 where an anticoagulant has been used. Most patients were treated using embolization where there was a clear bleeding focus [6][7][8][14][15][16]. In this study, no obvious bleeding focus was observed on the CT scan, and the ECMO flow was not properly maintained due to external compression by a huge RPH.…”
Section: Discussionmentioning
confidence: 84%
“…With the accumulation of data for severely ill patients with COVID-19, case reports of bleeding complications from the use of anticoagulant are being reported more frequently. Typically, these reports advise caution regarding the risk of bleeding [6][7][8][14][15][16], but despite the acknowledged risk of bleeding, the use of an anticoagulant for the stable use of ECMO is inevitable.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent locations were the retroperitoneum and the muscular abdominal walls [152][153][154][191][192][193][194][195] (Figure 27). The muscles most commonly affected were the iliopsoas and the rectus abdominis [152][153][154][191][192][193][194][195]. In most cases, patients were older, receiving a prophylactic dose of subcutaneous enoxaparin, and showed moderate-to-severe COVID-19 pneumonia.…”
Section: Hemorrhagic Abdominal Complicationsmentioning
confidence: 99%
“…Nevertheless, data over hemostasis disturbances related to COVID-19 are scarce in the medical literature [3,[9][10][11]. Except for the severe examples of disseminated intravascular coagulopathy observed in severe cases hospitalized in the intensive care units, further hemorrhages with diverse locations have been reported [12,13]. In the same vein, spontaneous hematomas developed in patients suffering or recovering from COVID-19 were rarely described [7,14], being mostly associated with the treatment with LMWH [1,9,11].…”
Section: Introductionmentioning
confidence: 99%